Digital cognitive tribes in classroom - Isabel Cristina Flores Rueda; José de Jesús Rodríguez-Sánchez; Beatriz Virginia Tristán Monrroy (Universidad de Guadalajara, 2024)
The aim of this research was to explore the possibility of conforming types of students, as well as to identify a possible relationship between the educational trajectory and the self-perception of both cognitive and technical skills. The research design was quantitative, transectional correlational. The analysis followed the structural equation model, hierarchical conglomerates and K-means, as well as a Chi-square hypothesis test. The information was collected from 191 university students, and the results showed three types of students that we called: analytical thinkers, progressing learners and technological innovators in addition to identifying a relationship between semester and cognitive skills as techniques. The studies that showed types of students based on cognitive and technical skills are rare and not very conclusive, although they focus on exploring different variables. This study was the first to address skills a priori of self-perceived cognitive and technical skills, as well as a description of the student environment based on different types for the possible application of multimodal courses, in addition to providing a key variable in high and positive self-perception: the semester.